2021
DOI: 10.1128/spectrum.01981-21
|View full text |Cite
|
Sign up to set email alerts
|

AdpA Positively Regulates Morphological Differentiation and Chloramphenicol Biosynthesis in Streptomyces venezuelae

Abstract: Streptomyces are well-known producers of valuable secondary metabolites which include a large variety of antibiotics and important model organisms for developmental studies in multicellular bacteria. The conserved transcriptional regulator AdpA of Streptomyces exerts a pleiotropic effect on cellular processes, including the morphological differentiation and biosynthesis of secondary metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…albulus . It’s recently reported that the posttranslational regulation is a possible new mechanism that may regulate AdpA protein abundance in Streptomyces cells [ 83 ]. Consequently, we surmise that regulation at the translational level by the UUA codon and posttranslational regulation might cause different AdpA protein abundances in the mutants studied in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…albulus . It’s recently reported that the posttranslational regulation is a possible new mechanism that may regulate AdpA protein abundance in Streptomyces cells [ 83 ]. Consequently, we surmise that regulation at the translational level by the UUA codon and posttranslational regulation might cause different AdpA protein abundances in the mutants studied in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the real mechanism is, it is useful practically because an improved dispersed growth of strains is one of the key requirements for industrial utilization. Curiously, the very recent data provided by Płachetka et al [64] have shown that the AdpA ortholog in Streptomyces venezuelae does not interact with its oriC region. Likely, this is one of the main factors explaining the dispersed growth common for S. venezuelae.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% of commercially important antibiotics are produced by this group of bacteria [2]. Some of the known antibiotics related to Streptomyces are streptomycin [3], tetracycline [4], chloramphenicol [5], kanamycin [6], fosfomycin [7], daptomycin [8], and platensimycin [9]. Besides the antibiotic group, Streptomyces can also produce antioxidant compounds such as thiazostatin A and B [10], protocatechualdehyde [11], and 2-(N-acetylcysteinyl)amido-2-deoxy-α-D-glucopyranosyl-myoinositol (U17) [12].…”
Section: Introductionmentioning
confidence: 99%